2021
DOI: 10.2196/22942
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a Virtual Reality–Based Simulation App (VR-MRI) With a Standard Preparatory Manual and Child Life Program for Improving Success and Reducing Anxiety During Pediatric Medical Imaging: Randomized Clinical Trial

Abstract: Background The experience of undergoing magnetic resonance imaging (MRI) can be anxiety provoking, particularly for pediatric patients and their families. Alternative methods to improve success and experiences without the use of sedation are needed. Objective This study aims to compare the effectiveness of a virtual reality (VR)—based simulation app (VR-MRI) with a standard preparatory manual (SPM) and a hospital-based Child Life Program (CLP) on succes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(95 citation statements)
references
References 65 publications
3
92
0
Order By: Relevance
“…Therefore, pediatric patients are prone to uncooperative behaviors such as crying and moving during Computed tomography (CT) or Magnetic Resonance Imaging (MRI) and other examinations associated with various equipment noises as well as cold, dim and claustrophobic environments. Such adverse emotions and uncooperation will significantly affect the implementation and effect of imaging examinations ( 1 ). Anxiety and fear can lead to increasing catecholamine levels in the body, causing tachycardia, increased airway secretions, shortness of breath; furthermore, the difficulty for children to separate from their parents and complete imaging examinations is risen ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pediatric patients are prone to uncooperative behaviors such as crying and moving during Computed tomography (CT) or Magnetic Resonance Imaging (MRI) and other examinations associated with various equipment noises as well as cold, dim and claustrophobic environments. Such adverse emotions and uncooperation will significantly affect the implementation and effect of imaging examinations ( 1 ). Anxiety and fear can lead to increasing catecholamine levels in the body, causing tachycardia, increased airway secretions, shortness of breath; furthermore, the difficulty for children to separate from their parents and complete imaging examinations is risen ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scanning these underrepresented populations requires thoughtful experimental accommodations. Some approaches for improving the likelihood of collecting usable data from pediatric participants focus on scan preparation: having a caregiver model scan procedures, practicing in an MRI simulator ( Horien et al, 2020 ; Nordahl et al, 2016 ; Simhal et al, 2021 ), or playing a virtual reality-based MRI game ( Pua et al, 2020 ; Stunden et al, 2021 ). Others focus on modifications during the scan: passive movie-viewing to reduce boredom ( Vanderwal et al, 2019 ), providing real-time feedback to participants using framewise integrated real-time MRI monitoring (FIRMM) software ( Dosenbach et al, 2017 ; Greene et al, 2018 ), or using personalized incentive systems to reward compliance with MRI instructions ( Pua et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scanning these underrepresented populations requires thoughtful experimental accommodations. Some approaches for improving the likelihood of collecting usable data from pediatric participants focus on scan preparation: having a caregiver model scan procedures, practicing in an MRI simulator (Nordahl et al, 2016; Horien et al, 2020; Simhal et al, 2021), or playing a virtual reality-based MRI game (Stunden et al, 2021; Pua et al, 2020). Others focus on modifications during the scan: passive movie-viewing to reduce boredom (Vanderwal et al, 2019), providing real-time feedback to participants using framewise integrated real-time MRI monitoring (FIRMM) software (Dosenbach et al, 2017; Greene et al, 2018), or using personalized incentive systems to reward compliance with MRI instructions (Pua et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies with autistic children have observed that head motion, while reduced after extensive training, is still associated with symptom severity (Simhal et al, 2021; Gabrielsen et al, 2018). Virtual reality-based games played at home may be as effective as MRI simulator training for typically developing children, (Stunden et al, 2021); however, it remains unclear if children with neurodevelopmental disorders would respond similarly. Investigating in-scanner strategies, Greene et al (2018) found that passive movie-viewing and real-time feedback both reduced head motion, but movie-viewing changed functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation